2001
DOI: 10.1267/ahc.34.371
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Related Changes in Skeletal Muscle Fiber Type and Insulin Resistance in Diabetic Otsuka Long-Evans Tokushima Fatty Rats.

Abstract: We investigated whether a relationship exists between the fiber type distribution in skeletal muscles and the insulin resistance of different ages of diabetic rats. The fiber type distributions of the slow soleus and fast plantaris muscles in 5-, 9-, and 21-week-old male Otsuka LongEvans Tokushima Fatty (OLETF) rats as an animal model of spontaneous type 2 diabetes mellitus were examined and compared with those in age-matched nondiabetic Long-Evans Tokushima Otsuka (LETO) rats. In the soleus muscle, a higher p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
42
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 41 publications
(54 reference statements)
7
42
1
Order By: Relevance
“…This conversion from type 1 to type 2A fibers may be caused by the reduction of load continuously resisted by the masseter muscle on the denervated side, occurring simultaneously with disuse atrophy of type 1 fibers. Conversion of slow fibers to fast fibers has previously been observed in the limb muscles [10,37] and during growth [20].…”
Section: Discussionmentioning
confidence: 67%
“…This conversion from type 1 to type 2A fibers may be caused by the reduction of load continuously resisted by the masseter muscle on the denervated side, occurring simultaneously with disuse atrophy of type 1 fibers. Conversion of slow fibers to fast fibers has previously been observed in the limb muscles [10,37] and during growth [20].…”
Section: Discussionmentioning
confidence: 67%
“…Patients with type 2 diabetes have a reduced number of high-oxidative fibers in their skeletal muscles [36][37][38] . This is linked with the glucose level because the growth-related increase in the glucose level in diabetic animals is associated with the number of low-oxidative fibers in skeletal muscles [39][40][41] . The mRNA expression level of PGC-1 in skeletal muscles is lower in diabetic patients than in healthy individuals 42) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fiber oxidative enzyme activity increased after hyperbaric exposure, regardless of fiber type. It is concluded that altered patterns of fiber types in the plantaris muscle of diabetic rats shift toward normal, which is observed in nondiabetic rats, following hyperbaric exposure with high oxygen concentration.Key words: diabetes mellitus, hyperbaric oxygenation, plantaris muscle.Patients and animal models with type 2 diabetes mellitus exhibit altered patterns of fiber types in skeletal muscles [1][2][3][4][5]. Goto-Kakizaki rats, animal models of spontaneous type 2 diabetes mellitus [6], have a lower percentage of high-oxidative fibers in the slow soleus and fast plantaris muscles than age-matched nondiabetic rats [7].…”
mentioning
confidence: 99%
“…Patients and animal models with type 2 diabetes mellitus exhibit altered patterns of fiber types in skeletal muscles [1][2][3][4][5]. Goto-Kakizaki rats, animal models of spontaneous type 2 diabetes mellitus [6], have a lower percentage of high-oxidative fibers in the slow soleus and fast plantaris muscles than age-matched nondiabetic rats [7].…”
mentioning
confidence: 99%